The Influence of Serbia’s Historical Constitutions on its Modern Constitutional Identity: – 30 Years Since the Return of Liberal Democratic Constitutionality – - Petrov, Vladan; Đorđević, Miroslav (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
Any kind of future constitutional development of one country is in large part bound by the constitutional tradition and ever-lasting constitutional development of the country in question. Determining the right milestones, long term historical trends and traces of surviving constitutional identity markers presents a daring quest for a constitutional law scholar, especially when a country that is subjected to such analysis has a rich, but quite diverse constitutional history, as the Republic of Serbia. In this chapter authors strive to discover distinctive periods of the Serbian constitutionality, examine their characteristics and establish a possible connection of historical constitutions to the present Serbian constitutional identity KEYWORDS: Serbian Constitution, Constitutional Identity, Historical Constitutions, Legal History, Constitutional Law, Liberal Democracy.